The philosophy of autism - Anderson, Jami L.; Cushing, Simon, 1968- (Rowman & Littlefield Publishers, 2013)
This book examines autism from the tradition of analytic philosophy, working from the premise that Autism Spectrum Disorders raise interesting philosophical questions that need to be and can be addressed in a manner that is clear, jargon-free, and accessible. The goal of the original essays in this book is to provide a philosophically rich analysis of issues raised by autism and to afford dignity and respect to those impacted by autism by placing it at the center of the discussion.